2002
DOI: 10.1002/eat.10028
|View full text |Cite
|
Sign up to set email alerts
|

Attentional biases and frontal functioning in anorexia nervosa

Abstract: This evidence suggested that in the AN-R subjects the disturbances of body image might be linked to the alterations of abstraction and critical abilities and with an obsessive frontal functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
84
4
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 35 publications
10
84
4
8
Order By: Relevance
“…36 Other studies have suggested impaired neuronal circuitry and orbitofrontal cortex involvement in AN. [37][38][39] There has been a paucity of studies directly comparing neuropsychological functioning in AN and BN participants. 8,40 A study comparing underweight and ''weight-recovered'' AN, normal weight BN and NC participants reported impaired attention in underweight AN and BN, impaired visuospatial function and memory in underweight AN and poorer focusing and executive functioning in BN.…”
Section: Introductionmentioning
confidence: 99%
“…36 Other studies have suggested impaired neuronal circuitry and orbitofrontal cortex involvement in AN. [37][38][39] There has been a paucity of studies directly comparing neuropsychological functioning in AN and BN participants. 8,40 A study comparing underweight and ''weight-recovered'' AN, normal weight BN and NC participants reported impaired attention in underweight AN and BN, impaired visuospatial function and memory in underweight AN and poorer focusing and executive functioning in BN.…”
Section: Introductionmentioning
confidence: 99%
“…Este es el caso, por ejemplo, de los estu- dios sobre la anorexia (Fassino, Piero, Daga, Leombruni, Mortara y Rovera, 2002), el trastorno obsesivo compulsivo (Head, Bolton y Hymas, 1989) o el trastorno antisocial de la personalidad (Deckel, Hesselbrock y Basuer, 1996).…”
unclassified
“…In other study, visuospatial deficits in the AN group were found (Mathias & Kent, 1998). In a trial of executive functions such as abstraction and the use of strategies in patients with AN and using the Wisconsin Card Sorting Test, Fassino et al (2002) found that patients with AN showed problems of abstraction and thinking flexibility, similar to those seen in patients with obsessive compulsive disorder. Altered body image showed a direct correlation with frontal alterations.…”
Section: Executive Functionning and Eating Disordersmentioning
confidence: 71%
“…Several studies have shown that patients with ED take longer time to name the color of words related to food, body shape and weight, compared with control participants (BenTovim et al, 1989;Channon et al, 1988;Fairburn et al, 1991;Fassino et al, 2002). Additionally, Cooper and Fairburn (1993) found that in the case of patients with BN, the interference is caused by the frequency of purging and not by the general psychiatric symptoms, however, Black et al (1997) consider that the differences between bulimic patients and normal controls, do not establish a specific cognitive impairment in these patients.…”
Section: Attention and Eating Disordersmentioning
confidence: 99%